Gene- Vitamin D Interaction and Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs)
Evidence for a role of vitamin D and direct gene-environmental interaction in the cause of multiple sclerosis (MS) is reviewed by researchers at John Radcliffe Hospital, Oxford, UK.